2015
DOI: 10.1007/s10665-015-9803-0
|View full text |Cite
|
Sign up to set email alerts
|

Viscous fingering in yield stress fluids: a numerical study

Abstract: The effect of yield stress is numerically investigated on the viscous fingering phenomenon in a rectangular Hele-Shaw cell. It is assumed that the displacing fluid is Newtonian, while the displaced fluid is assumed to obey the bi-viscous Bingham model. The lubrication approximation together with the creeping-flow assumption is used to simplify the governing equations. The equations so obtained are made two-dimensional using the gap-averaged variables. The initially flat interface between the two (immiscible) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…essentially taking into account the behavior of the material in its liquid regime. This led to detailed instability criteria and descriptions and analysis of various trends (Coussot 1999, Fontana et al 2013, Ebrahimi et al 2016. The validation of these conclusions by confrontation with experimental data remains extremely limited, and when this was done a reasonable agreement for the finger size (Lindner et al 2000, Derks et al 2003, Maleki-Jirsaraei et al 2005, but a strong discrepancy was found concerning the instability criterion (Barral et al 2010), suggesting some important effect is missed.…”
Section: Saffman-taylor Instabilitymentioning
confidence: 98%
“…essentially taking into account the behavior of the material in its liquid regime. This led to detailed instability criteria and descriptions and analysis of various trends (Coussot 1999, Fontana et al 2013, Ebrahimi et al 2016. The validation of these conclusions by confrontation with experimental data remains extremely limited, and when this was done a reasonable agreement for the finger size (Lindner et al 2000, Derks et al 2003, Maleki-Jirsaraei et al 2005, but a strong discrepancy was found concerning the instability criterion (Barral et al 2010), suggesting some important effect is missed.…”
Section: Saffman-taylor Instabilitymentioning
confidence: 98%
“…Heavy oils are also viscoplastic due to the presence of a high amount of asphaltenes and resins. Viscoplastic behaviors are present in industrial applications such as petroleum and chemical processing, the pulp and paper industry, food, and cosmetics, as well as in everyday life such as spreading butter over toast, squeezing toothpaste from tubes, cleaning mud from shoes, and using cosmetic creams . As yield stress materials resist motion in rectangular cell displacement flows, the presence of a yield stress is expected to significantly affect the interface and the flow patterns. …”
Section: Introductionmentioning
confidence: 99%
“…Thus this EOR process can take place in the low permeability zone which otherwise would be bypassed in a conventional gas flooding. A great number of laboratory and numerical investigations have been performed to approve the effectiveness of the foam flooding worldwide in recent years (Ebrahimi et al, 2016;Haugen et al, 2014;Jian et al, 2012;Thorat and Bruining, 2016;Wang et al, 2011).…”
Section: Résumé -éValuation Et Optimisation D'une Technique De Rah Hymentioning
confidence: 99%